2013
DOI: 10.3238/arztebl.2013.0737
|View full text |Cite
|
Sign up to set email alerts
|

The Orthotic Treatment of Acute and Chronic Disease of the Cervical and Lumbar Spine

Abstract: No definitive evidence as yet supports the use of orthoses after spinal interventions or in painful conditions of the cervical or lumbar spine. They should, therefore, be used only after individual consideration of the indications in each case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
0
14
0
4
Order By: Relevance
“…Appropriate lumbar lordosis decreases disc pressure by changing the distribution of the load between the disc and apophyseal joints and also reduces the tension in the intervertebral ligaments that can cause disc degeneration 9 , 10 ) . Wearing a lumbar support may increase intra-abdominal pressure that can decrease disc pressure, limit disc compression, and reduce disc pain 11 ) . To create a better back supporter, the lumbar spinal curvature of an individual should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate lumbar lordosis decreases disc pressure by changing the distribution of the load between the disc and apophyseal joints and also reduces the tension in the intervertebral ligaments that can cause disc degeneration 9 , 10 ) . Wearing a lumbar support may increase intra-abdominal pressure that can decrease disc pressure, limit disc compression, and reduce disc pain 11 ) . To create a better back supporter, the lumbar spinal curvature of an individual should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Against this, Zarghooni et al in their review found that orthoses are not recommended for nonspecific LBP. They should, therefore, be used only after individual consideration of the indications in each case [18]. The use of belts, corsets, or orthoses is frequently reported as an alternative therapeutic associated in LBP but without strong evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Although several reports were available with respect to cervico-thoracic devices, other groups of immobilizers completely lacked any reports or studies. This might be one of the reasons why there is no definitive evidence about the use of orthoses after spinal interventions or in painful conditions of the cervical spine [24].…”
Section: Discussionmentioning
confidence: 99%